Optimal Gender-Specific Strategies for the Secondary Prevention of Heart Disease in Women: A SYSTEMATIC REVIEW. Issue 5 (September 2018) - Rao, Angela; Newton, Phillip J.; DiGiacomo, Michelle; Hickman, Louise D.; Hwang, Christine; Davidson, Patricia M.
Abstract : Background: There is a paucity of evidence on gender-specific, individually tailored secondary prevention (cardiac rehabilitation [CR]) services for women with heart disease. Women participate less in CR programs, thus increasing their risk of further cardiac events. This review aims to (1) determine the effectiveness of gender-specific interventions specifically designed for women with heart disease, delivered in outpatient CR settings; and (2) classify key elements of effective CR strategies/models for women with heart disease. Methods: Using the PRISMA guidelines, this is a systematic review of CR models tailored to women to improve cardiovascular risk. Four databases were searched for randomized controlled trials (RCTs) between January 1974 and July 2017 published in peer-reviewed English language journals. Results: Three RCTs comprising 725 women of gender-specific CR strategies were identified. Significant improvements were found in one-third (1 study) of the included multicomponent CR strategies for outcomes including general health, social functioning, vitality, mental health, depression, and quality of life. Conclusion: Further large-scale RCTs are required to replicate positive findings and accurately assess the capacity for gender-specific multicomponent CR programs that incorporate participant-driven collaborative models to moderate psychological risk and improve functional capacity and quality of life for women with heart disease. Abstract : Supplemental Digital Content is Available in the Text.Women participate less in cardiac rehabilitation and are at increased risk of further cardiac events. This systematic review of cardiac rehabilitation models tailored to women to improve cardiovascular risk identified 3 randomized controlled trials comprising 725 women. Preliminary efficacy was demonstrated in one-third of the genderspecific models tailored to women.